Mechanically‐Guided 4D Printing of Magnetoresponsive Soft Materials across Different Length Scale. (14th October 2021) - Zhu, Hanlin; He, Yifeng; Wang, Yuan; Zhao, Yan; Jiang, Chao
Abstract : Untethered magnetoresponsive soft materials that can transform between various complex 3D shapes are of growing interests in diverse areas such as soft robotics, flexible electronics, and biomedical engineering. Previous approaches are difficult to precisely encode continuous 3D magnetization profiles in small‐scale 3D structures. Herein, a novel method to produce magnetoresponsive soft materials for shape‐morphing systems across different length scale is reported. The magnetization profiles are programmed by the mechanically‐guided 4D printing with high precision and time‐cost efficiency. A theoretical model and model‐based simulation method are developed to quantitatively predict shape‐morphing of printed structures under applied magnetic fields, and guide the design of complex 3D shapes. A broad set of structures with complex transformations are fabricated to illustrate the capability of the methods. Diverse typical functional applications from centimeter‐ to millimeter‐scale, including soft crawling robots, flexible grippers, bionic butterfly, and multistate magnetic switch, are further demonstrated. Abstract : Mechanically‐guided 4D printing of magnetoresponsive soft materials is investigated with experiments, theoretical model, and numerical simulations. Magnetization profiles can be precisely programmed by the shape‐morphing process during 4D printing. The 4D‐printed soft materials can experience complex 3D transformations under applied magnetic field. Diverse functional applications from centimeter‐ to millimeter‐scale are demonstrated, such as soft crawling robots and flexible grippers.